Exploring the Effects of a Neck Strengthening Program on Purposeful Soccer Heading Biomechanics and Neurocognition - Katelyn M. Waring; Edward R Smith; Gary P Austin; Thomas G Bowman (International Journal of Sports Physical Therapy)
# Background